TINJAUAN SISTEMATIS PENERAPAN SISTEM INFORMASI MANAJEMEN OPERASIONAL: ANALISIS LITERATUR MENGGUNAKAN PENDEKATAN PRISMA PADA ARTIKEL TERINDEKS SINTA TAHUN 2020–2025 - Itrizal Itrizal; Vicky Brama Kumbara (Ensiklopedia of Journal, 2026)
Operational Management Information Systems (MIS) have become an essential enabler for organizations across sectors—spanning manufacturing, financial services, retail, and healthcare—by strengthening business-process efficiency, data reliability, and the pace of decision-making. This review sets out to chart the trends, characteristics, and principal findings reported in Indonesian scholarly literature on Operational MIS adoption, drawing on SINTA-indexed journals published between 2020 and 2025. A Systematic Literature Review (SLR) design was adopted, guided by the 2020 Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. Literature was traced through Google Scholar, Garuda, and the SINTA portal using the combined search terms